Treatment of Water Contaminated with Polycyclic Aromatic Hydrocarbons (PAHs): A Review of Various Techniques, Constraints, and Field Procedures - Sambo, Godswill; Muhammad, Syahidah Akmal; Pyar, Hassan; Binhweel, Fozy (Chimica et Natura Acta, 2022)
Clean water is vital in the creation of energy and sustenance of life. However, the pollution of water and the absence of potable water are global problems resulting from agricultural and industrial activities. We have witnessed significant growth in the pollution of water by organic compounds like PAH. Experts have made an effort to establish favorable techniques for the treatment of PAH polluted water. These techniques are either thermal, biological, physical or chemical. Bioremediation, chemical oxidation, solid-phase extraction, coagulation, photocatalytic degradation and adsorption using graphenes, mesoporous silica and agricultural wastes are techniques that are already in use in the field treatment of PAHs while electrokinetic remediation and nanoremediation are still in their developmental stage. Several reviews on the treatment of sediments and soils contaminated with PAHs have been published, but only a few reviews center mainly on the removal of PAHs in water. Therefore, this review aims to provide information on the techniques used in the treatment of water contaminated with PAHs. Techniques that are already in use and those that are in their developmental stage were reviewed. The successes of these methods, limitations, constraints and field procedures were analyzed and this will help to inform decision making.